Genetic profile of adaptive immune traits and relationships with parasite resistance and productivity in Scottish Blackface sheep - A. Pacheco; J. Conington; Y. Corripio-Miyar; D. Frew; G. Banos; T.N. McNeilly (Animal, 2024)
Gastrointestinal (GI) parasites cause significant production losses in grazing ruminants which can be mitigated by breeding animals resistant to disease. Lymphocyte cytokine production and parasite-specific Immunoglobulin A (IgA) are adaptive immune traits associated with immunity to GI parasites. To explore the utility of these traits for selective breeding purposes, this study estimated the genetic parameters of the immune traits in sheep and assessed their relationship with disease and productivity traits. Whole blood stimulation assays were performed on 1 040 Scottish Blackface lambs at two months of age in 2016–2017. Blood was stimulated with either pokeweed mitogen (PWM), a non-specific activator of lymphocytes, and Teladorsagia circumcincta (T-ci) larval antigen to activate parasite-specific T lymphocytes. The type of adaptive immune response was determined by quantifying production of cytokines interferon-gamma (IFN-γ), interleukin (IL)-4, and IL-10, which relate to T-helper type (Th) 1, Th2 and regulatory T cell responses, respectively. Serum T-ci specific IgA was also quantified. Heritabilities were estimated for each immune trait by univariate analyses. Genetic and phenotypic correlations were estimated between different immune traits, and between immune traits vs. disease and productivity traits that were recorded at three months of age. Disease phenotypes were expressed as faecal egg counts (FEC) of nematode parasites (Strongyles and Nematodirus), faecal oocyst counts (FOC) of coccidian parasites, and faecal soiling score; production was measured as lamb live weight. Significant genetic variation was observed in all immune response traits. Heritabilities of cytokine production varied from low (0.14 ± 0.06) to very high (0.77 ± 0.09) and were always significantly greater than zero (P < 0.05). IgA heritability was found to be moderate (0.41 ± 0.09). Negative associations previously identified between IFN-γ production and FOC, and IL-4 production and strongyle FEC, were not evident in this study, potentially due to the time-lag between immune and parasitology measures. Instead, a positive genetic correlation was found between FOC and PWM-induced IFN-γ production, while a negative genetic correlation was found between FOC and T-ci induced IL-10. Live weight was negatively genetically correlated with IFN-γ responses. Overall, IFN-γ and IL-4 responses were positively correlated, providing little evidence of cross-regulation of Th1 and Th2 immunity within individual sheep. Furthermore, T-ci specific IgA was highly positively correlated with PWM-induced IL-10, indicating a possible role for this cytokine in IgA production. Our results suggest that while genetic selection for adaptive immune response traits is possible and may be beneficial for parasite control, selection of high IFN-γ responsiveness may negatively affect productivity.